1999
DOI: 10.1109/60.815122
|View full text |Cite
|
Sign up to set email alerts
|

Neural network based control for synchronous generators

Abstract: In this paper, a Radial Basis Function neural network based AVR is proposed. A control strate0 which generates local linear models from a global neural model on-line is used to derive controller feedback gains based on the Generalised Minimum Variance technique.Testing is carried out on a micromachine system wbich enables evaluation of practical implementation of the scheme. Constraints imposed by gathering training data, computational load, and memory requirements for the training algorithm are addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…The discussers would like to know the authors' comments on the following issues in the paper: 1 1) In the introduction the authors indicate the paper 1 as a maiden attempt to design an RBF network based adaptive PSS (RB-FAPSS). In [1] a RBF network is used to find the control parameters for an excitation controller with generalized minimum variance controller (GMV). In [2] a scheme for combining backpropagation neural network with conventional PID control is proposed.…”
Section: Discussion Of "Radial Basis Function (Rbf) Network Adaptive mentioning
confidence: 99%
See 2 more Smart Citations
“…The discussers would like to know the authors' comments on the following issues in the paper: 1 1) In the introduction the authors indicate the paper 1 as a maiden attempt to design an RBF network based adaptive PSS (RB-FAPSS). In [1] a RBF network is used to find the control parameters for an excitation controller with generalized minimum variance controller (GMV). In [2] a scheme for combining backpropagation neural network with conventional PID control is proposed.…”
Section: Discussion Of "Radial Basis Function (Rbf) Network Adaptive mentioning
confidence: 99%
“…This fact has been clearly stated in the paper. 1 Further, it may be noted that the results reported it Table II of the paper 1 have been obtained for SSE = 0.1 for all the cases studied. It is appropriate to highlight the fact that number of RBF centers chosen by OLS technique from the training set increases with the reduction in the value of SSE, which is pre-specified, for the training.…”
Section: ) the Training Time Of The Rbf Network Increases Steeply Wimentioning
confidence: 89%
See 1 more Smart Citation
“…A number of papers have been published in the last decade. An illustrative list of example papers include (Abido & Abdel-Magid, 1999;Changaroon, Srivastava, & Thukaram, 2000;Hiyama & Lim, 1989;Hosseinzadeh & Kalam, 1999;Segal, Kothari, & Madnani, 2000;Swidenbank et al, 1999;Yuan & Chao, 1991). Both of these techniques have their own advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 96%
“…Parameters of an adaptive stabilizer are adjusted on-line according to the operating conditions. Many years of intensive studies have shown that the adaptive stabilizer can provide good damping over a wide operating range (Pierre 1987;Shi-jie et al 1986a,b;Chen et al 1993;Segal et al 2000;Hosseinzadeh and Kalam 1999;Zhang et al 1993) and can also work in coordination with CPSSs (Chaturvedi et al 2004a;Swidenbank et al 1999).…”
mentioning
confidence: 97%